2018
DOI: 10.3390/en11113196
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Roofing Methods: Construction Features, Heat Reduction, Payback Period and Climatic Responsiveness

Abstract: The roofs of buildings play an essential role in energy efficiency because a significant amount of solar radiation is absorbed by roofs in hot weather and a significant amount of heat is lost through roofs in cold weather. This paper is a systematic literature review about roofing methods for flat roofs. Ten roofing methods are reviewed in this paper. They are concrete roof, cool roof, insulated roof, roof garden, photovoltaic panels’ roof, biosolar roof, double-skin roof, roof ponds, skylight roof, and wind c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…Vegetated roofs mitigate the heat flux through the roof by shading the roof surface with plants, evapotranspiration of the plants, and the additional thermal insulation and mass, which are caused by the growing media [4]. There is a wide range of investigations that show the other advantages of green roofs such as reduction of stormwater runoff [5][6][7][8] as a Low Impact Development (LID) option, urban heat island effects [9][10][11], sound insulation [6,12], enhancement of the life span of a roof [13], creation habitats for species, and improving air quality by absorbing CO 2 and producing O 2 [14][15][16][17][18][19][20]. Due to the aforementioned benefits of green roofs, many local authorities in different countries have implemented the policy for using green roofs in new buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetated roofs mitigate the heat flux through the roof by shading the roof surface with plants, evapotranspiration of the plants, and the additional thermal insulation and mass, which are caused by the growing media [4]. There is a wide range of investigations that show the other advantages of green roofs such as reduction of stormwater runoff [5][6][7][8] as a Low Impact Development (LID) option, urban heat island effects [9][10][11], sound insulation [6,12], enhancement of the life span of a roof [13], creation habitats for species, and improving air quality by absorbing CO 2 and producing O 2 [14][15][16][17][18][19][20]. Due to the aforementioned benefits of green roofs, many local authorities in different countries have implemented the policy for using green roofs in new buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In the consulted literature, it was found that many envelope studies are related directly to energy savings in tertiary and residential buildings [14]; therefore, profound analysis for industrial buildings is still needed. A large number of studies are carried out for hot and warm climates [15]. Valuable studies like the case studies in Austria for refurbishment [16], in Slovakia for a quantification of the energy demand [17], and a nearly zero-energy buildings study for the steel sector in Germany [18]; point out the following: most of the reviewed literature consists on case studies and generalizations are still required [14], and that for cold climates, an increase of insulation thickness is not cost-effective [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, almost half of buildings' energy is consumed for thermal performance purposes [3]. Therefore, high-performing building envelopes are needed to meet energy efficient buildings [4]. Taking this into consideration, cool roof technology is a widely acknowledged strategy for building thermal-energy performance improvement, by acting mainly on energy requirement for cooling [5,6] and urban heat island (UHI) phenomenon mitigation [7,8].…”
Section: Introductionmentioning
confidence: 99%